Fundamentals of Entrepreneurship ENT300 : Business plan Tera Center Printing and Photocopy Services / Luka Elvis... [et al.] - Luka, Elvis; Faridy, Nazuand Afrie; Kamil, Mohd Azizi (Universiti Teknologi MARA Sarawak,Kampus Samarahan, 2020)
The name of our business is TERA CENTER. Tera means" huge". From the shared ideas from members, we agree to choose "TERA CENTER" as our business name which mean we want to be a huge business in the future. We provide printing and photocopy service sin University of Technology Mara (UiTM) Sarawak. Tera Centre aims to produce high quality printing and photocopy . Besides, we want to ensure that our services will satisfy our costumer and be the different services Company among the companies at there.